Investigating the Relationship between Employee Well-being Programs and Organizational Performance - Hidayat, Muhammad; Rahwana, Kusuma Agdhi (Penelitian dan Pengembangan Ilmu, 2024)
This research investigates the relationship between employee wellness programs and organizational performance in various industrial sectors. Using literature analysis methods, this research analyzes recent studies that explore the impact of employee welfare programs on organizational performance. The main findings show that employee wellness programs have a significant role in increasing job satisfaction, productivity, and employee retention in industrial sectors such as manufacturing, information technology, health services, and education. The implication of this research is that a better understanding of the effectiveness of employee wellness programs can help organizations design more effective wellness strategies according to the specific needs of each industry sector, taking into account factors such as company size, organizational culture, and company policies.